Analisis Yuridis dalam Tradisi Brandu di Kabupaten Gunungkidul Berdasar Kajian Sociological Jurisprudence - Harahap, Nurmalita Ayuningtyas (University of Merdeka Malang, 2024)
Brandu or porak is a tradition of slaughtering sick or dead livestock and selling the meat to reduce losses for livestock owners. The problems of this research include, firstly, why do people in Gunungkidul Regency still carry out the brandu tradition even though it has been prohibited by positive law in Indonesia, secondly what the brandu problem is if analyzed using sociological jurisprudence, thirdly, what should the government's efforts to overcome this problem be if linked to analysis using sociological jurisprudence. Research Method uses a doctrinal approach and constructivist paradigm. People in Gunungkidul Regency still carry out the brandu tradition because the poverty rate is still high, besides that, the people of Gunung Kidul are known to have a high level of empathy towards each other, especially if their neighbors experience difficulties and suffering due to the death of livestock. In the Brandu case, if analyzed using the sociological jurisprudence school, it shows that positive law and the traditions that live in society are equally important, so it is hoped that in the formation of law and law enforcement, positive law and law in society must be taken into account in harmony. The government's efforts to overcome this problem should be that the government needs to form legal policy products to overcome brandu.